Appraisals of the Bangladeshi Medicinal Plant Calotropis gigantea Used by Folk Medicine Practitioners in the Management of COVID-19: A Biochemical and Computational Approach - Dutta, Mycal; Nezam, Mohammad; Chowdhury, Subrata; Rakib, Ahmed; Paul, Arkajyoti; Sami, Saad Ahmed; Uddin, Md. Zia; Rana, Md. Sohel; Hossain, Shahadat; Effendi, Yunus; Idroes, Rinaldi; Tallei, Trina; et al. (Frontiers in Molecular Biosciences, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first recognized in Wuhan in late 2019 and, since then, had spread globally, eventually culminating in the ongoing pandemic. As there is a lack of targeted therapeutics, there is certain opportunity for the scientific community to develop new drugs or vaccines against COVID-19 and so many synthetic bioactive compounds are undergoing clinical trials. In most of the countries, due to the broad therapeutic spectrum and minimal side effects, medicinal plants have been used widely throughout history as traditional healing remedy. Because of the unavailability of synthetic bioactive antiviral drugs, hence all possible efforts have been focused on the search for new drugs and alternative medicines from different herbal formulations. In recent times, it has been assured that the Mpro, also called 3CLpro, is the SARS-CoV-2 main protease enzyme responsible for viral reproduction and thereby impeding the host’s immune response. As such, Mpro represents a highly specified target for drugs capable of inhibitory action against coronavirus disease 2019 (COVID-19). As there continue to be no clear options for the treatment of COVID-19, the identification of potential candidates has become a necessity. The present investigation focuses on the in silico pharmacological activity of Calotropis gigantea, a large shrub, as a potential option for COVID-19 Mpro inhibition and includes an ADME/T profile analysis of that ligand. For this study, with the help of gas chromatography–mass spectrometry analysis of C. gigantea methanolic leaf extract, a total of 30 bioactive compounds were selected. Our analyses unveiled the top four options that might turn out to be prospective anti–SARS-CoV-2 lead molecules; these warrant further exploration as well as possible application in processes of drug development to combat COVID-19.